The Role of Ethical Leadership in Enhancing Organizational Trust Among Principals of Primary Schools in Taif City. - Dradkeh, Amjad; Al-Mutairi, Huda (Jordan Journal of Educational Sciences, 2017)
This study aimed to identify the level of primary school principals practicing moral leadership and its role in the promotion of organizational confidence from the standpoint of teachers. It also investigated the degree of difference in these views depending on the specialization variables, educational qualification, years of experience, the supervisory office. Study sample consisted of (432) females who were selected randomly, and the results of the study indicated that all the moral leadership exercised by the directors of primary schools in Taif from the standpoint of the teachers was (very high). All organizational confidence exercised by the directors of primary schools in Taif from the standpoint of the teachers dimensions was (very high). There is a statistically significant positive relationship between the variables of moral leadership and all the fields, and between organizational trust and all fields. There are no significant differences between mean degrees of study sample in moral leadership and organizational confidence exercised by the directors of the primary stage from the standpoint of the teachers due to the variables level (specialization, academic qualification, years of experience, and the bureau supervisory)